2017
DOI: 10.1111/gwat.12619
|View full text |Cite
|
Sign up to set email alerts
|

Weathering of Oil in a Surficial Aquifer

Abstract: The composition of crude oil in a surficial aquifer was determined in two locations at the Bemidji, MN, spill site. The abundances of 71 individual hydrocarbons varied within 16 locations sampled. Little depletion of these hydrocarbons (relative to the pipeline oil) occurred in the first 10 years after the spill, whereas losses of 25% to 85% of the total measured hydrocarbons occurred after 30 years. The C6‐30 n‐alkanes, toluene, and o‐xylene were the most depleted hydrocarbons. Some hydrocarbons, such as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 50 publications
(86 reference statements)
1
24
0
Order By: Relevance
“…This is consistent with observations for near‐surface microbial activity in uncontaminated settings (Yuste et al ), including semiarid environments (Huxman et al ), although the timeframe for observing microbial response is shorter for such shallow environments (Kim et al ; Ford et al ). Alternatively, the additional soil moisture may not be important per se, but rather the percolating water may carry additional nutrients and electron acceptors downward to the LNAPL body for use in biodegradation (Bekins et al ; Baedecker et al ). Irianni‐Renno et al () identified the top of the LNAPL body and bottom of the vadose zone in a localized portion of this site as having a diverse microbiological community where such electron acceptor utilization may occur.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with observations for near‐surface microbial activity in uncontaminated settings (Yuste et al ), including semiarid environments (Huxman et al ), although the timeframe for observing microbial response is shorter for such shallow environments (Kim et al ; Ford et al ). Alternatively, the additional soil moisture may not be important per se, but rather the percolating water may carry additional nutrients and electron acceptors downward to the LNAPL body for use in biodegradation (Bekins et al ; Baedecker et al ). Irianni‐Renno et al () identified the top of the LNAPL body and bottom of the vadose zone in a localized portion of this site as having a diverse microbiological community where such electron acceptor utilization may occur.…”
Section: Resultsmentioning
confidence: 99%
“…As such, the LNAPL depletion ranged from 5 to 90% for each carbon number bucket, with an average of 30%. Having an average of 30% of the LNAPL deplete over only a 9-year period may be too high, based on the longevity of LNAPL at the Bemidji site (Baedecker et al 2018); possible reasons include: (1) the Douglas model assumes that these longer-chained compounds (>nC 11 constituents) are totally recalcitrant but there is likely some biodegradation of these compounds at the site, thereby make the Douglas model overpredict LNAPL depletion; (2) the monitoring well purging may have been incomplete so some of the LNAPL weathered more rapidly while in the monitoring well, and therefore does not completely represent the LNAPL in the subsurface;…”
Section: Lnapl Composition Change Over Timementioning
confidence: 99%
“…A number of studies have also demonstrated the important role of natural surface recharge in transporting rate‐limiting nutrients and EAs to groundwater. This process has been shown to exert an important control on natural attenuation of dissolved contaminants (McGuire et al ; van Stempvoort et al ), as well as methanogenic biodegradation of long chain alkanes in a crude oil body located in the shallow subsurface (Bekins et al ; Baedecker et al ).…”
Section: Introductionmentioning
confidence: 99%